Effects of far infrared radiation by isotropic high-density carbon on the human oral mucosa. (October 2018) - Kimura, Isao; Yamamoto, Toshiro; Nakamura, Koya; Uenishi, Toshihiro; Asai, Taku; Kita, Masakazu; Kanamura, Narisato
Highlights: Far infrared irradiation using isotropic high-density carbon significantly increased HSP 27 mRNA as compared with the control group. Far infrared irradiation using isotropic high-density carbon showed an increasing tendency of expression of HSP70 mRNA as compared with the control group. Immunostaining showed a strong positive response to Ki 67, HSP 27 and HSP 70 in the epithelium of the stimulation group. Far-infrared radiation emitted by isotropic high-density carbon promotes the production of heat shock proteins. Heat shock protein promotes regenerative response to oral mucosal injury. Abstract: Objectives: Wound healing of the oral mucosal epithelium through the application of far infrared radiation emitted by isotropic high-density carbon was investigated in order to clarify the preventive and therapeutic effects of isotropic high-density carbon on oral mucosal injury. Materials and methods: A carbon massager with an isotropic high-density carbon tip was used. Far infrared radiation was applied to the human buccal mucosal squamous cell carcinoma cell line, HO-1 -N- 1 using a carbon massager, and cell growth factors and heat shock protein levels were measured using real-time RT-PCR and ELISA. Far infrared radiation was applied to oral mucosal injury in SD rats over time using the carbon massager, and its effects were examined by HE staining and immunostaining. The immunostaining positive rate was measured and analyzed using image analysis software. Results: Far infrared radiation induced stronger mRNA expression and higher HSP27 and HSP70 protein levels on real-time RT-PCR and ELISA than in the control group. The far infrared radiation of oral mucosal injury in rats induced strong positive reactions, and positive rates for Ki67, HSP27, and HSP70 were higher than those in the control group. Conclusions: The treatment of oral mucosal injury with far infrared radiation emitted by isotropic high-density carbon appears to have promoted heat shock protein production and induced regenerative reactions more strongly than in the control group.